Analisis Perkembangan Bahasa Anak Usia 5-6 Tahun: Ditinjau dari Durasi Screen Time Perhari di Desa Mendalo Indah - Fitria Susanti; Rizki Surya Amanda; Winda Sherly Utami (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The advancement of information technology has increased young children’s exposure to digital devices, which potentially affects language development. This study aims to analyze the relationship between daily screen time duration and language development of children aged 5–6 years in Desa Mendalo Indah, Kecamatan Jambi Luar Kota, Kabupaten Muaro Jambi. This research employed a descriptive qualitative approach with a case study design. The subjects were six children aged 5–6 years who had more than two hours of daily screen time. Data were collected through observations of children’s language abilities, interviews with parents, and documentation of daily activities, and analyzed using Miles and Huberman’s (2014) interactive model, including data reduction, data display, and conclusion drawing. The results showed variations in children’s language abilities despite having relatively similar screen time durations. Children who received active parental guidance and accessed educational content demonstrated better receptive and expressive language skills, including following sequential instructions, forming simple sentences, and expressing ideas verbally. Conversely, children who used screen time passively without supervision tended to have limitations in vocabulary acquisition, concentration, and verbal interaction. These findings indicate that screen time duration alone is not the sole determinant of children’s language development; it is also influenced by the quality of parental guidance, the type of content accessed, and social interaction experiences. This study is expected to provide guidance for parents, teachers, and early childhood education practitioners in managing digital media use wisely to optimally support children’s language development.